ANALISIS SENTIMEN TERHADAP PEMUTUSAN HUBUNGAN KERJA DI INDONESIA : KOMPARASI INDOBERT DENGAN SVM, RANDOM FOREST, DAN DECISION TREE DENGAN OPTIMASI TF - IDF - Nida Nur Aini Aryanti; Ozzi Suria (LPPM Universitas Abdurrab, 2025)
Employment termination (PHK) has become a crucial issue widely discussed on social media platforms like Twitter due to its social and economic impacts. This study aims to analyze public sentiment toward PHK in Indonesia using four classification methods: IndoBERT, Support Vector Machine (SVM), Random Forest, and Decision Tree. The data were collected via Twitter crawling using the keyword